4CPS-020 Use and effectiveness of carboxymaltose iron and isomaltoside iron. (2nd March 2018) - Gómez, P Nieto; Sanchez, R Alvarez; Raya, P Moreno; Delgado, A Rodriguez
Abstract : Background: Carboxymaltoside-iron (CMI)and isomaltoside-iron (IMI)have both indications for the treatment of iron deficiency when oral preparations are ineffective or cannot be used. Purpose: To describe the use of CMI and IMI, and to evaluate its effectiveness and cost in a tertiary-level hospital. Material and methods: Retrospective observational study based on the analysis of the data obtained through the CMI and IMI prescriptions of 1 year. The main variable used to evaluate effectiveness was the percentage of patients with an increase in haemoglobin (HB) compared to baseline HB higher than 1 g/dL between 30 to 60 days' post-administration. The mean increase in HB (g/dL) by cumulative dose in the same period of time was the second variable. A search was made on our system, and sex, dose, posology, prescribing service, treatment with erythropoiesis stimulating factors (ESF) and direct cost per cumulative dose. Results: Thirty-one patients(13 females, 18 men) were treated with CMI and 35 (25 females and 10 men) with IMI. The median cumulative dose was 500 mg (500–1000) for CMI and 1000 (1000–1000) for IMI. The median cost per cumulative dose was €89 for CMI (89–178) and €148 (148–148) for IMI. Prescription services were: nephrology 25%, haematology 12.5%, cardiology 12.5%, digestive system 25%, surgery 6.25% and systemic diseases 18.75% for CMI compared to nephrology 45.45%, haematology 36.36% and cardiology 18.18% for IMI. The percentage of patients with an increase in HB compared to baseline HB higher than 1 g/dL:50% for CMI and 45.45% for IMI. Among patients on ESF treatment these percentages were 3125% for CMI and 27.27% for IMI. Mean increase of HB compared to baseline HB (g/dl) by cumulative dose: 1.04±2 for CMI and 0.73±1.29 for IMI (p=0.3) and among patients receiving ESF was 2.2±1.03 for CMI compared to 0.94±1.31 for IMI (p=0.046). Conclusion: The effectiveness in the patients studied was higher with CMI than with IMI because better results were observed with a lower cumulative dose. It was also observed that the effectiveness was higher in patients receiving ESF for both compounds, and it was statistically significant among patients on ESF treatment. In terms of use, the service with the greatest number of prescriptions in both compounds was nephrology. No conflict of interest